2022
DOI: 10.3390/ijms23042095
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of n-Butylidenephthalide on Retinal Ganglion Cells during Ischemic Injury

Abstract: Clinically, acute ischemic symptoms in the eyes are one of the main causes of vision loss, with the associated inflammatory response and oxidative stress being the key factors that cause injury. Nonarteritic anterior ischemic optic neuropathy (NAION) is the most common type of ischemic optic neuropathy (ION); however, there are still no effective or safe treatment options to date. In this study, we investigated the neuroprotective effects of n-butylidenephthalide (BP) treatment in an experimental NAION rodent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Nonarteritic anterior ischemic optic neuropathy (NAION) is a vexing problem for neuro-ophthalmologists because there is no effective prevention or treatment for it. Numerous unsuccessful therapeutic approaches include antiplatelet treatment, anticoagulation, calcium channel blockers, levodopa, memantine, anti-inflammatory agents, corticosteroids, growth factors, neuroprotective agents, optic nerve sheath fenestration, and hyperbaric oxygen (1). A greater understanding of the mechanisms leading to retinal ganglion cell death after an attack of NAION may open avenues for new treatments.…”
Section: Tsai Rk Lin Kl Huang Ct Wen Yt Transcriptomic Analysis Revea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonarteritic anterior ischemic optic neuropathy (NAION) is a vexing problem for neuro-ophthalmologists because there is no effective prevention or treatment for it. Numerous unsuccessful therapeutic approaches include antiplatelet treatment, anticoagulation, calcium channel blockers, levodopa, memantine, anti-inflammatory agents, corticosteroids, growth factors, neuroprotective agents, optic nerve sheath fenestration, and hyperbaric oxygen (1). A greater understanding of the mechanisms leading to retinal ganglion cell death after an attack of NAION may open avenues for new treatments.…”
Section: Tsai Rk Lin Kl Huang Ct Wen Yt Transcriptomic Analysis Revea...mentioning
confidence: 99%
“…This elegant study provides strong evidence that the TAF9 pathway is an important component of GCSF-induced neuroprotection of RGC. It takes its place alongside multiple other studies that demonstrate neuroprotective effects involving the inhibition of apoptosis by various molecules, including n-butylidenephthalide (1) and bardoxolone methyl (2) in rat models of NAION. The results provide hope for targeted antiapoptosis therapy for patients with NAION through upregulation of TAF9 at a time when vision-saving treatments are still desperately needed.…”
Section: Tsai Rk Lin Kl Huang Ct Wen Yt Transcriptomic Analysis Revea...mentioning
confidence: 99%
“…Huang demonstrated that Epimedium exerts anti-inflammatory effects in a rodent anterior ischemic optic neuropathy (rAION) model, inhibits nuclear factor-kappa B kinase to phosphorylate phosphatase and alleviate tensin homolog and activate threonine protein kinase (Akt) in response to ischemic stress ( Huang et al, 2020a ). Further research found that butylens benzonitrile can effectively prevent the apoptosis induced by rAION and that the inhibition of NF-κB signaling can reduce the inflammatory response of blood-derived macrophages infiltrating the optic nerve, thereby alleviating neuroinflammation and facilitating the improvement of RGCs ( Chou et al, 2022 ). The administration of Houttuynia cordata after retinal I/R injury has been found to inhibit the upregulation of TNF-α, inducible nitric oxide synthase (iNOS), and IL-1β in the treatment of ischemic events by activating microglia to promote the survival of RGCs ( Ren and Zhang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%